Supply and equipment in the Arctic. - Tennesson, Charles E., Jr. (Fort Leavenworth, KS : US Army Command and General Staff College, 1948)
This is a study on the essential supply and equipment problems important to military operations in the Arctic and recommends appropriate action based on this study. Subjects discussed include Arctic delimitation, importance of the Arctic, factors affecting Arctic operations, equipment, supply, and transportation problems.